Religiosität als erwünschte Anregung in der Hermeneutik - Janez Vodičar (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Paul Ricoeur insists on some kind of philosophical agnosticism although in everyday practice he is consciously bound to Christianity. That said, his poetical approach in Biblical hermeneutics when he confronts his position with his no believing contemporaries, very clearly shows that religious dimension of man, especially in its openness to new meanings, makes the understanding more proli fi c. This opens the way for new attempts of repeated search for human need for religious dimension also at Luc Ferry and Gianni Vattimo. It is not necessary that there is a very certain form of religiosity; the important thing is openness for these questions. In this way we liberate the science, to seriously confront with religious dimension of man. This is especially important in a globalized world where religiosity on one hand can be a cause for the clash of civilizations and on the other it can be a possibility of a common search for a world ethos.